Effects of information and communication technologies on international trade: a panel data analysis - Tabakan, Anıl. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2015., 2015)
Information and communication technologies (ICT) are considered as one of the key factors increasing the efficiency, productivity and the overall performance of the systems. This thesis aims to explore the increasing importance of ICT usage in international trade. Different indexes in measuring ICT usage are reviewed with their pillars and the top country rankings. Taking the Global Competitiveness Index 2014 as the source, the study investigates the effects of ICT usage on the integration of countries to the world trade by taking the countries’ export/GDP ratio as their integration indicator. The panel data is generated by taking 21 countries and nine years into account without time lag and seven years with two years of time lag. The results show that there is a significant positive relationship between ICT usage and a country’s export/GDP ratio. Especially, the number of fixed broadband connection subscriptions and quality of scientific research institutions are seen to be two of the most influential factors to affect the export/GDP ratio positively, while on the other hand, firms’ technology absorption and governments’ advanced technology procurement are the most negatively sub-pillars of ICT usage. Additionally, the FDI and the technology transfer seem to be candidates for being influential factors for the export/GDP ratio in the long run.
Keywords: Information and communication technologies.